p38 Mitogen-Activated Protein Kinase Is Critical for Synergistic Induction of the FSHβ Gene by Gonadotropin-Releasing Hormone and Activin through Augmentation of c-Fos Induction and Smad Phosphorylation - Coss, Djurdjica (2007)
GnRH and activin independently and synergistically activate transcription of the FSH β-subunit gene, the subunit that provides specificity and is the limiting factor in the synthesis of the mature hormone. This synergistic interaction, as determined by two-way ANOVA, is specific for FSHβ and may, therefore, contribute to differential expression of the two gonadotropin hormones, which is critical for the reproductive cycle. We find that the cross-talk between the GnRH and activin signaling pathways occurs at the level of p38 MAPK, because the synergy is dependent on p38 MAPK activity, which is activated by GnRH, and activin cotreatment augments p38 activation by GnRH. Both the Smad and activator protein-1 binding sites on the FSHβ promoter are necessary and sufficient for synergy. After cotreatment, Smad 3 proteins are more highly phosphorylated on the activin-receptor signaling-dependent residues on the C terminus than with activin treatment alone, and c-Fos is more highly expressed than with GnRH treatment alone. Inhibition of p38 by either of two different inhibitors or a dominant-negative p38 kinase abrogates synergy on FSHβ expression, reduces c-Fos induction by GnRH, and prevents the further increase in c-Fos levels that occurs with cotreatment. Additionally, p38 is necessary for maximal Smad 3 C-terminal phosphorylation by activin treatment alone and for the further increase caused by cotreatment. Thus, p38 is the pivotal signaling molecule that integrates GnRH and activin interaction on the FSHβ promoter through higher induction of c-Fos and elevated Smad phosphorylation.